β-lactam precision dosing in critically ill children: Current state and knowledge gaps - Tang Girdwood, Sonya; Pavia, Kathryn; Paice, Kelli; Hambrick, H. Rhodes; Kaplan, Jennifer; Vinks, Alexander A. (Frontiers in Pharmacology, 2022)
There has been emerging interest in implementing therapeutic drug monitoring and model-informed precision dosing of β-lactam antibiotics in critically ill patients, including children. Despite a position paper endorsed by multiple international societies that support these efforts in critically ill adults, implementation of β-lactam precision dosing has not been widely adopted. In this review, we highlight what is known about β-lactam antibiotic pharmacokinetics and pharmacodynamics in critically ill children. We also define the knowledge gaps that present barriers to acceptance and implementation of precision dosing of β-lactam antibiotics in critically ill children: a lack of consensus on which subpopulations would benefit most from precision dosing and the uncertainty of how precision dosing changes outcomes. We conclude with opportunities for further research to close these knowledge gaps.